Goats discriminate emotional valence in the human voice - Marianne A. Mason; Stuart Semple; Harry H. Marshall; Alan G. McElligott (Animal Behaviour, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Review of: Holland, M (2012) Social bonding and nurture kinship: compatibility between cultural and biological approaches. North Charleston: CreateSpace Independent Publishing - Stuart Semple (acta ethologica, 2016)

Towards bioavailability-based soil criteria: past, present and future perspectives - Ravi Naidu; Rufus Channey; Stuart McConnell; Niall Johnston; Kirk T. Semple; Steve McGrath; Victor Dries; Paul Nathanail; Joop Harmsen; Andrew Pruszinski; Janet MacMillan; Thavamani Palanisami (Environmental Science and Pollution Research, 2015)

Personality Traits in Rhesus Macaques (Macaca mulatta) Are Heritable but Do Not Predict Reproductive Output - Lauren J. N. Brent; Stuart Semple; Ann MacLarnon; Angelina Ruiz-Lambides; Janis Gonzalez-Martinez; Michael L. Platt (International Journal of Primatology, 2014)

Seasonal changes in the structure of rhesus macaque social networks - Lauren J. N. Brent; Ann MacLarnon; Michael L. Platt; Stuart Semple (Behavioral Ecology and Sociobiology, 2013)

Sexual Skin Color Contains Information About the Timing of the Fertile Phase in Free-ranging Macaca mulatta - Constance Dubuc; Lauren J. N. Brent; Amanda K. Accamando; Melissa S. Gerald; Ann MacLarnon; Stuart Semple; Michael Heistermann; Antje Engelhardt (International Journal of Primatology, 2009)

The timing of ovulation with respect to sexual swelling detumescence in wild olive baboons - James P. Higham; Michael Heistermann; Caroline Ross; Stuart Semple; Ann MacLarnon (Primates, 2008)

Gastrointestinal Parasites in Crop Raiding and Wild Foraging Papio anubis in Nigeria - Anna H. Weyher; Caroline Ross; Stuart Semple (International Journal of Primatology, 2006)